In Vitro Starch Digestibility and Total Carotenoid of Corn from Various Types of Processing - Rina Yenrina; Fauzan Azima; Rani Liganti; Heriyenni Heriyenni (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
This research aims to study in vitro starch digestibility, total carotenoid, and nutritional content from various ways of corn processing. The design used in this study was explorative with six treatments is raw, boiled, steamed, roasted, fried, and puffing. The results showed that the lowest water content was found in popcorn (0.93%), the lowest ash content in raw corn (0.52%), the lowest fat content in raw corn (0.61%), the highest protein content in raw corn (8.80%), the highest starch content in popcorn (59.19%), the lowest amylose content in fried corn (19.56%) and the highest amylopectin in fried corn (80.44%), FFA content (0.33%) in fried corn, the highest carotenoid content (11.05 μg/g) was found in raw corn and the lowest carotene content(6.01 μg/g) was found in popcorn, the lowest starch digestibility (47.36%) was found in raw corn